Do we miss rare adverse events induced by COVID-19 vaccination? - Mohseni Afshar, Zeinab; Tavakoli Pirzaman, Ali; Liang, Jackson J.; Sharma, Akanksha; Pirzadeh, Marzieh; Babazadeh, Arefeh; Hashemi, Erfan; Deravi, Niloofar; Abdi, Sadaf; Allahgholipour, Amirreza; Hosseinzadeh, Rezvan; Vaziri, Zahra; et al. (Frontiers in Medicine, 2022)
Although severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has caused many complications, the invention of coronavirus disease 2019 (COVID-19) vaccines has also brought about several adverse events, from common side effects to unexpected and rare ones. Common vaccine-related adverse reactions manifest locally or systematically following any vaccine, including COVID-19 vaccines. Specific side effects, known as adverse events of particular interest (AESI), are unusual and need more evaluation. Here, we discuss some of the most critical rare adverse events of COVID-19 vaccines.